(untitled) (Contemporary Journal of Social Science Review, 2024)
This study investigates the moderating effect of gender on vocabulary learning strategies and vocabulary achievement scores among high and low achievers. Utilizing SPSS and SMART PLS 4, the research aims to provide insights into the differential strategies employed by learners and their subsequent impact on achievement, while also considering the influence of gender. Data was collected from a sample of students, assessing their vocabulary learning strategies and corresponding achievement scores. Through statistical analysis, including regression and moderation analysis, the study reveals the nuanced relationship between gender, learning strategies, and achievement outcomes. Furthermore, it examines the distinct strategies utilized by high and low achievers, offering valuable insights into effective learning practices. Findings indicate that gender plays a significant moderating role in the relationship between vocabulary learning strategies and achievement, highlighting the need for tailored instructional approaches. Additionally, the analysis discerns specific strategies employed by high achievers, which differ from those utilized by low achievers, suggesting targeted interventions to enhance vocabulary acquisition. This research contributes to a deeper understanding of the complex interplay between gender, learning strategies, and vocabulary achievement, with implications for educational practice and policy.